Maximizing energy harvesting in grid-connected hybrid photovoltaic and thermoelectric generator systems: An adaptive global power tracking technique - Al‐Tawalbeh, Nedaa; Zafar, Muhammad Hamza; Abuishmais, Ibrahim; Mohd Zainuri, Muhammad Ammirrul Atiqi; Mohd Radzi, Mohd Amran (John Wiley and Sons, 2025)
This paper proposes an innovative strategy to optimize the integration of thermoelectric generator (TEG) and photovoltaic (PV) technologies into a hybrid system linked to a three-phase grid, aiming to enhance renewable energy harvesting and raise overall system efficiency. An adaptive overstepping tracking algorithm is presented to meet the requirements of hybrid PV-TEG systems for grid-connected applications, combining the advantages of conventional perturb and observe techniques with a modified trapezoidal rule based technique. The validations were conducted under a wide range of weather fluctuations, including varying irradiance, temperature gradients, complex partial shading levels, and dynamic sun irradiation. The results of the simulation show that the proposed method performs better than some of the most widely used metaheuristic approaches, exhibiting notable gains in energy yield of over 99.7% efficiency with a response time of less than 10 ms, reducing steady-state error (SSE) to less than 0.2%. Experimentally, the proposed technique has been put into practice and evaluated in a variety of additional weather scenarios using a solar simulator and a microcontroller (TMS320F28335) as the main part of the implemented setup. In all tests that were carried out, the reliable and stable response with an efficiency of over 99% was approved. The findings demonstrate that the adaptive MPPT technique can significantly enhance the stability and efficiency of solar systems, paving the way for more robust and high-performing renewable energy solutions.